2020
DOI: 10.1016/j.clnu.2019.04.006
|View full text |Cite
|
Sign up to set email alerts
|

The DALI vitamin D randomized controlled trial for gestational diabetes mellitus prevention: No major benefit shown besides vitamin D sufficiency

Abstract: M. N. M. (2020). The DALI vitamin D randomized controlled trial for gestational diabetes mellitus prevention: No major benefit shown besides vitamin D sufficiency. Clinical Nutrition, 39(3), 976-984. https://doi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 36 publications
4
50
0
3
Order By: Relevance
“…However, the optimal 25(OH)D levels for GDM prevention remain unknown. A European multicenter RCT of early intervention (before 26 th week of pregnancy) randomized women at risk for GDM (BMI ≥ 29 (kg/m 2 ) with various intervention arms, including diet+physical activity+vitamin D and vitamin D alone (DALI study) (134). Unfortunately, supplementation with 1,600 IU/day of vitamin D did not show a clear effect in reducing the risk of GDM.…”
Section: Nutritional Requirements and Role Of Nutraceuticals In Gdmmentioning
confidence: 99%
“…However, the optimal 25(OH)D levels for GDM prevention remain unknown. A European multicenter RCT of early intervention (before 26 th week of pregnancy) randomized women at risk for GDM (BMI ≥ 29 (kg/m 2 ) with various intervention arms, including diet+physical activity+vitamin D and vitamin D alone (DALI study) (134). Unfortunately, supplementation with 1,600 IU/day of vitamin D did not show a clear effect in reducing the risk of GDM.…”
Section: Nutritional Requirements and Role Of Nutraceuticals In Gdmmentioning
confidence: 99%
“…Whether any of the associations we have identified reflect a causal relationship and whether vitamin D supplementation might modulate PE risk for women with diabetes are unknown. A recent study showed a marginal reduction in fasting glucose with vitamin D supplementation but was underpowered to address PE [53]. In that study, in contrast to our T1DM patients, the women were largely vitamin D sufficient at study entry.…”
Section: Discussionmentioning
confidence: 62%
“…Evidence from one of these meta-analyses suggested that pregnancies with low blood vitamin D had a higher risk of GDM (odds ratio 1.85) and that vitamin D supplementation during pregnancy significantly reduced fasting plasma glucose (FPG), fasting insulin levels, and HOMA-IR [ 24 ]. On the other hand, results from the Diabetes and Pregnancy Vitamin D and Lifestyle Intervention for Gestational Diabetes Mellitus Prevention (DALI) European multicenter randomized controlled trial found only a minor beneficial effect of vitamin D supplementation on glucose metabolism [ 26 ]. These discrepancies might be due to differences in baseline vitamin D concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in the review by Zhang et al [ 24 ], a positive effect of vitamin D concentration was seen among RCTs where the participants were vitamin D deficient and vitamin D doses in the intervention arm were high [ 24 , 27 ]. In contrast, the DALI study population had higher rate of vitamin D sufficiency at baseline and showed a minimal effect of vitamin D supplementation on markers of GDM development [ 26 ]. In the current review, participants from the three included RCTs had 25(OH)D concentration <50 nmol/L at baseline, with participants in the intervention arms reaching vitamin D insufficiency in one RCT [ 17 ] and sufficiency in the two others [ 20 , 21 ], while the control groups remained deficient.…”
Section: Discussionmentioning
confidence: 99%